A Prospective Multicenter Study for Assessing MusiQoL Validity among Arabic-Speaking MS Patients Treated with Subcutaneous Interferon β-1a. (2nd March 2021) - Al Jumah, Mohammed; Kojan, Suleiman; Alroughani, Raed; Cupler, Edward; Bohlega, Saeed; Daif, Abdulkader; Al Mujalli, Mousa; Al Harbi, Talal; El Tamawy, Mohamed; Ashour, Samia; Mhiri, Chokri; Gouider, Riadh; et al.
Abstract : Few studies examine health-related quality of life (HRQoL) in Arabic-speaking multiple sclerosis (MS) patients. However, HRQoL tools such as the Short Form-36 QoL instrument (SF-36) and the Multiple Sclerosis International QoL (MusiQoL) questionnaire have been validated in other languages. The primary objective of this study was to prospectively assess HRQoL using the MusiQoL questionnaire among Arabic-speaking MS patients treated with subcutaneous interferon (sc IFN β -1a) over 12 months, as part of a prospective, multinational, multicenter cohort study. Patients' clinical parameters and HRQoL were assessed at baseline, 6 months, and 12 months. Changes in MusiQoL total and subdomain scores were compared using a Friedman test. Correlation between MusiQoL total score and Expanded Disability Status Score (EDSS) was also evaluated. In total, 439 patients from four Arabic-speaking countries were included. The mean age was 32.44 (±0.34) years, 71.5% were female, and 63.1% had an education level of university or above. The mean MS duration was 4.13 (±0.12) years, mean age at first attack was 27.35 (±0.26) years, and mean baseline EDSS score was 2.05 (±0.04). MusiQoL total score significantly improved at 6 months; however, this diminished at 12 months (65.67 ± 0.8 at baseline vs. 67.21 ± 0.79 at 6 months and 65.75 ± 0.8 at 12 months; p = 0.0015 ). Several aspects of patients' HRQoL including activity of daily living, physical well-being, symptoms, and coping improved. Overall HRQoL measured using SF-36 remained generally unchanged over time (p = 0.215 ). There was a statistically significant inverse relationship between change in EDSS score over time and change in overall MusiQoL score over time. In summary, findings confirm the utility of using MusiQoL for assessing changes in HRQoL during treatment with sc IFN β -1a in Arabic-speaking patients with MS.